Technology takes the wheel analyzing distracted driving mindset while driving focusing on selfie while driving / Siti Sarah Mansor - Mansor, Siti Sarah (Faculty of Art and Design, 2015)
The purpose of this study is to analyze the bad and dangerous phenomenon when people take a shoot "selfie" when driving. To realize about this issue, I build a campaign on " Don't Selfie While Driving". In addition, this study attempts to show the understanding about distracted driving mindset while driving focusing on selfie while driving. Selfie phenomenon is become nowadays trend. Thus the most appropriate research design for this thesis was a quantitative study. The interview questionnaire were open-ended to ask and acquire knowledge about people on the consequences when selfie while driving and to make sure this kind of distracted driving must be demolished.